Pan Narrans: architecture and 21st century storytelling - Benade, Rudi (My University, 2011)
Humans are storytelling creatures, not Homo Sapiens but Pan Narrans: The Storytelling Chimpanzee. The story is told by one human to another and thus finds another place to take hold. Furthermore, the story is written down or recorded and then exists inside media. Storytelling is a method for ensuring that knowledge and ideas exist outside of the human head. Through this process humanity becomes ‘extelligent’. Architecture is used as an interface to our stories: portals are built to regain access to them. The theatre has been the oldest of such portals, being found in some form or another since 2500 BC. As media evolve and accumalate, the theare has grown into a conglomerate of portals: today a theatre typically encompasses a library or archive, a cinema, a gallery, as well as the stage for performance. Storytelling has now been altered by a the Net: a total-medium. Suddenly all media exist together as one. Books, films, images and conversation all travel through the same network. The storytellers are altered as well. The means of production are now availble to everyone. Anyone can be storyteller (again). The Read-Write capability of the Net makes switching from spectator to actor instant. The advantages of virtual media come at the cost of tangibility and interpersonal contact. Without comparative discussion we risk allowing these disadvantages to be ‘lockedin’ indefinitely. This thesis therefore discusses the requirements of a portal to stories in the 21st Century. As case studies, a number of flexible ‘theatre machines’ are investigated to suggest how this portal might manifest. The traditional theatre is condensed and adapted to suit the needs of its new medium and become a Web Theatre Comlex. Finally such a design concept is proposed at an intervention site in Braamfontein, Johannesburg